Endogenous productivity and development accounting - Roc Armenter; Amartya Lahiri (Federal Reserve Bank of New York, 2006)
Cross-country data reveal that the per capita incomes of the richest countries exceed those of the poorest countries by a factor of thirty-five. We formalize a model with embodied technical change in which newer, more productive vintages of capital coexist with older, less productive vintages. A reduction in the cost of investment raises both the quantity and productivity of capital simultaneously. The model induces a simple relationship between the relative price of investment goods and per capita income. Using cross-country data on the prices of investment goods, we find that the model does fairly well in quantitatively accounting for the observed dispersion in world income. For our baseline parameterization, the model generates thirty-five-fold income gaps and sixfold productivity differences between the richest and poorest countries in our sample.
Keywords: O11; F43; O33; O41; 330; cross-country income; productivity; vintage capital; Produktivität; Wachstumstheorie; Technischer Fortschritt; Vintage-Modell